Guidelines for improvement of the procedural aspects of devices and surgical instruments in the operating theatre - Calò, P. G.; Catena, F.; Corsaro, D.; Costantini, L.; Falez, F.; Moretti, B.; Parrinello, V.; Romanini, E.; Spinarelli, A.; Venneri, F.; Vaccaro, G., Scientific Technical Committee; et al. (Frontiers in Surgery, 2023)
Surgical site infections are a major complication for patients undergoing surgical treatment and a significant cause of mortality and morbidity. Many international guidelines suggest measures for the prevention of surgical site infections (SSI) in perioperative processes and the decontamination of surgical devices and instruments. This document proposes guidelines for improving the perioperative setting in view of the devices and instrumentation required for surgical procedures, aiming to reduce contamination rates and improve clinical performance and management for patients undergoing surgical treatment. This document is intended for doctors, nurses and other practitioners involved in operating theatre procedures, resource management and clinical risk assessment processes, and the procurement, organization, sterilization and reprocessing of surgical instruments.